Evaluation of Hypervolemia in Children - Kopač, Matjaž (Journal of Pediatric Intensive Care, 2020)
Hypervolemia is a condition with an excess of total body water and when sodium (Na) intake exceeds output. It can have different causes, such as hypervolemic hyponatremia (often associated with decreased, effective circulating blood volume), hypervolemia associated with metabolic alkalosis, and end-stage renal disease. The degree of hypervolemia in critically ill children is a risk factor for mortality, regardless of disease severity. A child (under 18 years of age) with hypervolemia requires fluid removal and fluid restriction. Diuretics are able to increase or maintain urine output and thus improve fluid and nutrition management, but their benefit in preventing or treating acute kidney injury is questionable.
Keywords: hypervolemia; kidney injury; children